(untitled) (Estudos em Design, 2024)
The complexity of the world requires from Design and Designers new capabilities to better respond to societal needs. Beyond the ability to identify and solve problems, thinking strategically becomes central to support transformative social innovations. These systemic environments demand from universities new education paths fordesigners by creating opportunities to collaborate with wide communities, in a meaningful fashion. Based on systematic and non-systematic reviews, this research aims to present an Interdisciplinary Third Mission UniversityProgram Proposal, guided by the Strategic design approach as a Boundary Object. The program combines the idea of four levels of actions (within the four missions of the university) to achieve a socially responsible model that works as an open system towards social transformation.